An Analysis Of Students’ Motivation And Their Achievement In Learning English At The Department Of English Education - Putri, Eka Nova; Mahdavi, Milad; Awlqadir, Mohammed Sherko (Journal of Language, Literature, and Educational Research, 2025)
Purpose of the study: This study aims to identify the dominant type of motivation integrative or instrumental among students learning English and to investigate whether these motivation types affect students' academic achievement (GPA). Methodology: This quantitative study utilized a survey method involving 89 first-year students from the Department of English Education. Data was gathered using 20 items from Gardner’s Attitude and Motivation Test Battery (AMTB), adapted to identify integrative and instrumental motivation. Statistical analysis was used to examine differences in GPA based on motivation types. Main Findings: The findings show that 56.2% of students have instrumental motivation while 43.8% have integrative motivation. However, statistical analysis revealed no significant difference in GPA between the two groups. Novelty/Originality of this study: This study contributes to understanding how different types of motivation (integrative vs. instrumental) relate to academic outcomes in an Indonesian tertiary EFL context.